The Role of E-Trust and E-Service Quality in Building E-Loyalty and E-Satisfaction - Lena Ellitan; Ani Suhartatik (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
The development of the internet in the modern era has an impact on changing people's lifestyles, including in terms of shopping, namely online shops. With the presence of this online shop, people originally preferred to shop directly facing the seller and see the goods they wanted to buy, now people are starting to switch to using online shopping facilities so that with internet-based technology, buyers and sellers do not need to meet face to face in carrying out the transaction process. The presence of e-commerce people easily promote their products through social media, but there is a drawback to this online shopping activity, where sellers and buyers do not meet in person, so trust is very important in determining whether or not transactions occur. In talking about marketplaces and e-commerce, the main thing that must be considered is e-trust. This is because there is no direct interaction between sellers and prospective buyers when shopping online on a marketplace and e-commerce sites. In connection with improving services by internet networks, the development of e-service quality was carried out. E-service qualiy is the development of the capabilities of a site in order to realize the effectiveness and efficiency of shopping, purchasing and product distribution facilities. Satisfaction with good service quality will be achieved if the reality is in accordance with consumer expectations. E-satisfaction is an assessment of the good and bad of the seller's service in meeting consumer expectations, which is carried out after the use of the product. Buyback of a product often occurs in consumers who assess the online shop site positively, conversely, if the assessment is lacking, the possibility of consumers changing brands is even greater. In online maintenance, consumers today really see all aspects related to products and services so that they don't just buy. The higher the level of satisfaction on an e-commerce site, the higher the loyalty that occurs. E-trust and e-service quality are the main keys in building e-satisfation and e-loyalty